Performance of OFDM‐based massive MIMO OTFS systems for underwater acoustic communication. Issue 4 (1st March 2020) - Bocus, Mohammud Junaid; Doufexi, Angela; Agrafiotis, Dimitris
Abstract : In this study, multi‐user (MU) underwater acoustic communication is investigated using massive multiple‐input multiple‐output (MIMO) orthogonal frequency division multiplexing (OFDM)‐based orthogonal time frequency space modulation (OTFS) systems. The performance of a 4‐user scenario is evaluated over a simulated 1 km vertically‐configured time‐varying underwater acoustic channel (UAC) in terms of bit error rate and maximum achievable bit rate. Considering 64‐QAM and frequency‐domain pilot‐based channel estimation, it is shown that the underwater vehicles employing the OFDM‐based OTFS modulation outperform those using the conventional OFDM modulation in a dynamic UAC. The application of massive MIMO allows the four underwater vehicles to use the same time and frequency resources to transmit their information reliably to a surface station. Furthermore, it is shown that each underwater vehicle in the MU‐massive MIMO transmission scenario can achieve an effective bit rate as high as 198.7 kbps over the 1 km UAC using four transmitting transducers.